1996
DOI: 10.1007/bf02029546
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation pheromone system of nymphal gregarious desert locust,Schistocerca gregaria (forskål)

Abstract: Hexanal, octanal, nonanal, decanal, hexanoic acid, octanoic acid, nonanoic acid, and decanoic acid were identified in the volatile emissions from fifth instars ofSchistocerca gregaria by coupled gas chromatography-electroantennography (GC-EAD) detection and coupled GC-mass spectrometry (MS). In laboratory assays, synthetic blends of the eight compounds, with acids and aldehydes tested separately, evoked strong aggregation responses from fifth instars, similar to responses evoked by a crude volatile extract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 10 publications
0
54
0
Order By: Relevance
“…(Acari: Ixodidae) and a potential attachment Benzaldehyde stimulant (Norval et al 1991a,b) and an attractant for some ticks (Yunker et al 1992). Key component of adult desert locust, Schistocerca gregaria Forskal (Orthoptera: Acrididae), aggregation pheromone blend (Torto et al 1994;Njagi et al 1996). Oviposition deterring component in the larval frass of Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) (Anderson et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Acari: Ixodidae) and a potential attachment Benzaldehyde stimulant (Norval et al 1991a,b) and an attractant for some ticks (Yunker et al 1992). Key component of adult desert locust, Schistocerca gregaria Forskal (Orthoptera: Acrididae), aggregation pheromone blend (Torto et al 1994;Njagi et al 1996). Oviposition deterring component in the larval frass of Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) (Anderson et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Part of the sex pheromone of the olive fruit fly, Dacus oleae (Gmelin) (Diptera: Tephritidae) (Mazomenos & Haniotakis, 1985). Aggregation pheromone component in both adult and nymphal desert locust, Schistocerca gregaria (Obeng-Ofori et al Guaiacol 1994;Torto et al 1994;Njagi et al 1996;Torto et al 1996); adult maturation retardant in the same insect (Assad et al 1997). Sex pheromone component of olive fruit fly, Dacus oleae (Mazomenos & Haniotakis 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the bird-cherry-oat aphid, RIzopalosiphurn padi L., the desert locust, Schistocerca gregaria Forskal, the greater wax moth, Galleria rnellonella (L.), the saw toothed grain beetle, Oryzaephillrts surirtamensis (Ti. ), the rus t y grain beetle, Cryptolestes ferrugineus (Stephens), the flat grain beetle, C. pusillus (Schonherr) and the tropical bont tick, Amblyomma variegaturn F. (Pierce et al 1990;Mushobozy et al 1993;Turker et al 1993;Steullet and Guerin 1994;Torto et al 1996;Assad et al 1997;Quiroz and Niemeyer 1998). Nonanal in the volatiles of plants acts as an allelochernic that inhibits seed germination (Bradow and Connick 1990) and probably serves in defence against pathogens and phytophagous insects due to its antifungal properties (Andersen et al 1994) as well as cytotoxic and genotoxic effects (Eck1 et al 1993;Martelli et al 1994).…”
Section: Ob) Detection Of Tram-verbenol From the Volatiles Of Poolmentioning
confidence: 99%
“…These observations have been confirmed by similar studies (Simpson et al, 2001;Lester et al, 2005). Pheromones play a role in the control of behavior in locusts (Loher, 1990;Byers, 1991;Pener, 180 S. TANAKA 1991; Pener and Yerushalmi, 1998) and their chemical structures and significance were intensively studied in the last decade (Torto et al, 1994(Torto et al, , 1996Ferenz and Seidelmann, 2003;Hassanali et al, 2005). Recently, it was demonstrated that prolonged pre-copulatory mounting increases the length of copulation, which in turn increases the P 2 , the proportion of offspring sired by the second male to mate, in L. migratoria showing multiple mating .…”
Section: Phase Polyphenismmentioning
confidence: 61%